Light input and processing in the circadian clock of Neurospora - Schafmeier, Tobias; Diernfellner, Axel (FEBS letters, 2011)
Circadian clocks are endogenous oscillators that use zeitgebers as environmental cues to synchronise with the exogenous day-night cycle. The role of light as a zeitgeber has been investigated intensively to date. In Neurospora crassa the transcription factor White Collar Complex (WCC) is directly activated by light, which resets the clock. In addition, a hierarchical cascade of transcription factors activates the light-induced expression of hundreds of genes. Disturbance of the clock during the day through changes in light intensity should be prevented to ensure efficient synchronisation. This can be achieved by desensitisation to the ambient light (photoadaptation). Photoadaptation in Neurospora is dependent on the blue light receptor Vivid (VVD), which accumulates immediately after light activation and rapidly silences the expression of WCC-dependent genes. Recent studies have elucidated the molecular mechanism of VVD-mediated photoadaptation. Here we review the increasing knowledge about light-dependent gene expression and photoadaptation in Neurospora and discuss their relevance for synchronisation of the circadian clock.